AN ANALYSIS OF STUDENTS’ TRANSLATION WORKS OF A BARACK OBAMA’S POLITICAL SPEECH - Wulan Nur’azizah (Journal of English and Education, 2015)
This study was concerned with analysis of translation strategies used by the students in translating a political speech of Barrack Obama, the difficulties faced by them in translating it and the quality of the translation works. This study used a descriptive-qualitative method with document analysis technique, using the theory of translation strategy proposed by Vinay Darbelnet (in Fawcett, 1997, pp. 34-9; in Bell, 1991, pp. 70-71) and Newmark (1988). While in terms of difficulties faced by the students in translating a text, it was done by examining vocabulary problem, lexical problem, and syntactic problem This study also used the NAATI’s assessment method to find out the quality of students’ translation works. The results show that the students employ several strategies in translating a political speech and the problem faced by them was complicated since political speech was contained sophisticated words and unfamiliar diction, therefore it was affecting the quality of the translation works.